Strategi Kepemimpinan Tuan Guru dalam Mewujudkan Lulusan yang Berkualitas di MDQH NWDI Pancor Lombok Timur - Nasrullah, Nasrullah (Lembaga Yasin AlSys, 2021)
This study aims to provide an overview of the role and function of non-formal religious education institutions in the current global era, it is hoped that they will be able to play an active role in instilling or internalizing religious values to students. In this article, we will examine the leadership strategy carried out by the teacher so that later it will have implications for students who have quality graduates. After understanding the teacher's leadership strategy, it is hoped that it can become a reference and example for leaders in both formal and non-formal institutions, namely in particular to produce ulama cadres.